Slovenian social support networks in a long-term perspective, 1987-2018 - Iglič, Hajdeja (Družboslovne razprave, 2019)
This article examines the effects of macro-level processes - economic recession, growth of the service economy, and deindustrialisation - on the social support networks of residents of Slovenia in the period between 1987 and 2018. Before the transition, Slovenia enjoyed highly functional social support networks. The economic downturns of the early 1990s and late 2000s increased the probability of insufficient social support. The growth of the service economy saw the importance grow of formal sources of support. Socio-demographic changes captured by the notion of the post-industrialisation of society brought various effects: the increased educational level and diminished size of households impacted the growing presence of formal sources and mixed social ties in support networks, while the ageing population contributed to the increased presence of networks with insufficient social support. We conclude that Slovenian social support networks have experienced a distinct transformation over the last three decades.
Keywords: Družbena omrežja; Družbeni procesi; Social networks; Social processes; Social support; Socialna opora